An Epidemiological Study of Psychiatric Cases in a Rural Community of Nepal - Khattri, JB; Poudel, BM; Thapa, P; Godar, ST; Tirkey, S; Ramesh, K; Chakrabortty, PK (Nepal Journal of Medical Sciences, 2013)
Background: Psychiatric cases are widespread in rural communities of Nepal and there is scarcity of data. The present work was undertaken to study the psychiatric cases and its association with different socio-demographic variables. Methods: A house to house survey was done with simple random method (n=261) in Kusmi Village Development Committee of Baglung District. A semi-structures proforma was used to record the socio-demographic variables and General Health Questinnaire-12 (GHQ-12) was administered to assess the psychiatric cases. Results: The overall prevalence of psychiatric cases was found to be 37.5 percent. The psychiatric cases were found more in age above 30 years, in males and in other caste (Dalit/Nepali). The maximum number of cases was also elicited in unskilled workers, married group and people who were using alcohol. Conclusion: The study concludes that there is high prevalence of psychiatric cases in rural community in Nepal. This also calls the need to strengthen the mental health services in the rural community and to address the risk factors associated with psychiatric cases. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 52-56 DOI: http://dx.doi.org/10.3126/njms.v2i1.7654